1998
DOI: 10.1002/(sici)1521-3757(19980817)110:16<2298::aid-ange2298>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation von Alkanen durch elektrophile späte Übergangsmetalle in homogener Lösung

Abstract: Die selektive Oxidation von Alkanen ist für Chemiker in Industrie und Hochschule ein Thema von größter Bedeutung. Die Alkanoxidation wurde bereits vor 25 Jahren entdeckt, doch haben neue Entwicklungen dieser Reaktion, katalysiert durch elektrophile, späte Übergangsmetalle, sowohl wichtige Erkenntnisse über den Mechanismus als auch potentiell in der Praxis anwendbare Methoden zur Umwandlung von Alkanen geliefert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Subsequent mechanistic studies have confirmed that 16electron platinum(iv) complexes are intermediates in most reductive ± elimination reactions that lead to CÀH [11] or CÀC [12,13] bond formation, as well as in the opposite CÀH [5,6,14] or CÀC [15] bond activation reactions by oxidative addition to platinum(ii) centers. They have also been proposed as intermediates in aor b-elimination reactions from alkylplatinum(iv) complexes, [16] in alkyl transfer reactions, [12] and in skeletal rearrangements of platina(iv)cyclobutane complexes.…”
Section: -Electron Platinum(iv) Complexes As Reaction Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent mechanistic studies have confirmed that 16electron platinum(iv) complexes are intermediates in most reductive ± elimination reactions that lead to CÀH [11] or CÀC [12,13] bond formation, as well as in the opposite CÀH [5,6,14] or CÀC [15] bond activation reactions by oxidative addition to platinum(ii) centers. They have also been proposed as intermediates in aor b-elimination reactions from alkylplatinum(iv) complexes, [16] in alkyl transfer reactions, [12] and in skeletal rearrangements of platina(iv)cyclobutane complexes.…”
Section: -Electron Platinum(iv) Complexes As Reaction Intermediatesmentioning
confidence: 99%
“…However, the catalytic systems were then too complex to allow study of the individual steps. [5,6] At that time alkylplatinum(iv) compounds were already known, and the reductive elimination to form platinum(ii) compounds by C À C bond reductive elimination was established. [7] Since this is the microscopic reverse of the alkane activation step of Scheme 1, the mechanism of the reductive elimination was studied.…”
mentioning
confidence: 99%
“…In accord with the diastereoselective outcome from labelling studies on ( E )‐ and ( Z )‐9a‐d 1 , the final step of C–N bond formation must proceed with inversion of configuration in order to account for the overall stereochemistry of the cyclic urea products 10a‐d 1 . An S N 2 transition state 16 , reminiscent of the one from the platinum(IV)‐catalysed methane oxidation in the related Shilov reaction,21,22 was suggested for this step. The required nucleophilicity of the nitrogen anion and its capacity for previous dissociation from the palladium centre confirms the design of the N‐tosylated urea.…”
Section: Intramolecular Diamination Of Alkenesmentioning
confidence: 99%
“…The chemistry of platinum hydrides has been a field of active research for more than 50 years. , With the platinum atom in oxidation state II or IV, many examples with Pt−H bonds were characterized . In particular, platinum(IV) hydrides were obtained by protonation of platinum(II) complexes or oxidative addition of hydrogen halides or element hydrides such as Me 3 SnH, GeH 3 Cl, PhSiH 3 , o -C 6 H 4 (SiH 3 ) 2 , or Et 3 SiH. In recent decades, platinum hydrides have received much attention especially with regard to catalytic C−H activations. Although organoplatinum(IV) hydrides are postulated as intermediates in these reactions, only few characterized examples of organoplatinum(IV) hydrides exist. ,,,, …”
Section: Introductionmentioning
confidence: 99%